(untitled) (The International Journal for Scientific Research, 2023)
192 specimens of the Saurida undosquamis were collected from the local market of Misurata city in Libya. the prevalence rate of cestode helminths in examined fish Saurida undosquamis, was high. Based on the morphological and morphometric characterization represented two species of cestodes were isolated. Of the total examined fish (169, 88%) were infected with (Tetraphyllidean sp. and Trypanorhyncha sp. larvae). The density of cestode helminths was around 6810, and they were collected from the stomach, anterior and posterior parts of the intestine in all seasons, the liver and muscles showed no cestode infection, and a non-significant difference (P> 0.05) were found between cestode density infection of infected organs, this study found a high infection rate with Tetraphyllidean sp. and Trypanorhyncha sp. larvae in the Saurida undosquamis.